Case Report: Respiratory paralysis associated with polymyxin B therapy - Ning, Yachan; Chu, Yanqi; Wu, You; Huang, Ying; Wang, Chunmei; Jiang, Li (Frontiers in Pharmacology, 2022)
Polymyxin-B (PMB) and colistin are bactericidal polypeptide antibiotics discovered in 1947 and 1949 for the treatment of gram-negative bacterial infections. Polymyxin was used clinically in the 1950s, but it was gradually replaced by other antibiotics in the 1980s because of its high nephrotoxicity and neurotoxicity. In recent years, the increase of multidrug-resistant negative bacteria has led to the resurgence of polymyxin use. But its side effects are not clear. Respiratory paralysis caused by PMB-related neuromuscular blockade is a rare but potentially fatal effect. We report a case of respiratory paralysis probably caused by polymyxin-B infusion.